PROPUESTA DE UN PLAN DE MARKETING TURISTICO PARA LOS ATRACTIVOS NATURALES Y CULTURALES DEL CANTON ATAHUALPA, PROVINCIA DE EL ORO - Díaz Ríos, Soraya Andrea (2016)
El Oro province whose cantonal head is the city of Machala, it is known for being known worldwide as the “Capital Bananera del Mundo”. It is considered as a privileged place since it has a nature, it owns an enormous tourist potential of global relief. The province has 14 cantons, where we can find the Atahualpa canto, the same that has been chosen for the development of the thesis project, the canton is distributed in one urban parish and five rural parishes. The present investigation has the purpose of contributing the touristic and socio-economic development in the canton, through the elaboration of a “TOURISM MARKETING PLAN FOR NATURAL AND CULTURAL ATTRACTIONS OF THE ATAHUALPA CANTON, EL ORO PROVINCE", so we have compiled important information during the same, on each of the attractions. To develop this Thesis Project, it was necessary to set out a general objective that was "Develop a marketing plan for natural and cultural attractions, contributing to the tourism and socio-economic development of the Atahualpa canton, El Oro” and the specific objectives are : 1. To make a diagnosis of the current situation of natural and cultural attractions of the Atahualpa canton; 2. To propose a marketing plan for the Atahualpa canton, allowing positioning as a tourist destination ; and 3.To socialize the proposed marketing plan with the respective authorities of the Atahualpa canton, for it local and national broadcast level. The methodology used allowed me to comply with each of the objectives, the methods that were used: deductive, inductive, descriptive, historical, and bibliographic. The techniques used were: the interview, addressed to the Mayor of the Atahualpa canton, and the survey was for the population of the canton, and also it was applied a direct observation and proceeded to perform a SWOT (FODA) analysis. To obtain the results of the first objective it was necessary to gather the bibliography, surveys and interviews; making the diagnosis through internal and external analysis of the Canton and the attractive; likewise the inventory card of the Ministry of Tourism attractions were filled. For the results of the second objective it was considered the information obtained in the first objective, which they were obtained four strategic objectives that allowed shaping the marketing plan, here the deductive, descriptive and historical methods were used, the same that facilitated 5 consider possible and better strategies for implementing the Marketing Plan. Finally, for the third objective it was made the socialization of the two previous objectives using slides and didactic material later to make relevant conclusions and recommendations Thus it was completed the elaboration of possible projects that can be performed and in this way to generate a contribution in the touristic field as natural and cultural attractions that has the Atahualpa canton did not have the corresponding spread for tourism development. Finally, it is concluded that the canton has poor infrastructure and suitable touristic services for the comfort of visitors, maintains natural and cultural attractions with great value, particularly for its history. Several of the attractions need maintenance, promotion and signage, in addition there should be more staff training local tourist service offering and guidance. The recommendations are directed to the Autonomous Decentralized Government of the Atahualpa canton responsible of the touristic management, the aim with this is to contribute to the tourism development in the canton and placed the tourism as a source of income in the economic sector of the Atahualpa canton.